2022
DOI: 10.1101/2022.05.16.492099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information integration for nutritional decision-making in desert locusts

Abstract: 1AbstractSwarms of the migratory desert locust can extend over several hundred square kilometres, and starvation compels this ancient pest to devour everything in its path. Theory suggests that gregarious behaviour benefits foraging efficiency over a wide range of spatial food distributions. However, despite the importance of identifying the processes by which swarms locate and select feeding sites to predict their progression, the role of social cohesion during foraging remains elusive. We investigated the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Locusts have been used to study olfactory [40][41][42][43] , visual 44 , social [45][46][47] , odor-sampling 48 , and foraging 49 behavior. However, it is yet to be shown that they are able to take advantage of surface-bound odor trails for navigation, which seems particularly relevant given their known swarming/aggregation behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Locusts have been used to study olfactory [40][41][42][43] , visual 44 , social [45][46][47] , odor-sampling 48 , and foraging 49 behavior. However, it is yet to be shown that they are able to take advantage of surface-bound odor trails for navigation, which seems particularly relevant given their known swarming/aggregation behavior.…”
Section: Discussionmentioning
confidence: 99%